1988
DOI: 10.1038/ki.1988.207
|View full text |Cite
|
Sign up to set email alerts
|

Immunological aspects of acute ureteral obstruction: Immune cell infiltrate in the kidney

Abstract: Kidneys from rats subjected to bilateral ureteral obstruction (BUO), unilateral ureteral obstruction (UUO) and UUO with subsequent release were analyzed for leukocyte infiltration. A time-dependent influx of leukocytes, predominantly macrophages and suppressor T lymphocytes, occurred in both the cortex and medulla following obstruction, and disappeared with release of the obstruction. Glomerular macrophages declined following obstruction but increased to levels above control following release. The influx of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
109
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(120 citation statements)
references
References 12 publications
7
109
0
4
Order By: Relevance
“…In both disease models the number of infiltrating macrophages and T cells was strongly reduced by Fab A77 treatment. Most leukocytes found in diseased kidneys are recruited from the circulation (43,44). In the UUO model, we showed by means of adoptive transfer experiments with Fc␣RI transgenic macrophages that Fab A77 treatment directly inhibited the influx of these cells.…”
Section: Discussionmentioning
confidence: 95%
“…In both disease models the number of infiltrating macrophages and T cells was strongly reduced by Fab A77 treatment. Most leukocytes found in diseased kidneys are recruited from the circulation (43,44). In the UUO model, we showed by means of adoptive transfer experiments with Fc␣RI transgenic macrophages that Fab A77 treatment directly inhibited the influx of these cells.…”
Section: Discussionmentioning
confidence: 95%
“…[23][24][25] Earlier studies have shown that macrophage/monocyte infiltration occurred in the kidney 4 h after acute ureteral obstruction and its peak response occurred at 24 h after UUO and stabilized thereafter. 26 Another study also showed a highly significant correlation between the increasing number of interstitial macrophage/monocyte and the cortical TGF-b mRNA levels. 27 Taken together, these results suggest that macrophage/monocyte is one potential source for the increased gene expression of TGF-b.…”
Section: Discussionmentioning
confidence: 97%
“…14) (5,20,21,27,33,35). Gradual dilation of renal tubules and flattening of epithelial cells were also observed in the present study.…”
Section: Tgf-f3 Immunostainingmentioning
confidence: 99%
“…Many investigators have reported reactive cells involved in an early phase of obstruction in the kidneys of rats and rabbits (3, 5, 15,20,27,33); increased numbers of macrophages, T lymphocytes, and myofibroblasts have been observed. However, the appearance of macrophages and myofibroblasts during chronic phases of fibrosis caused by long-term ureteral obstruction has not been described in detail.…”
Section: Introductionmentioning
confidence: 99%